The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.4103/1735-5362.329922
|View full text |Cite
|
Sign up to set email alerts
|

Oxypeucedanin and isoimperatorin extracted from Prangos ferulacea (L.) Lindl protect PC12 pheochromocytoma cells from oxidative stress and apoptosis induced by doxorubicin

Abstract: Background and purpose: Doxorubicin (DOX) as a chemotherapeutic agent has been widely used in the treatment of various types of cancer. However, DOX exerts a toxic effect on normal tissues such as the brain. Furanocoumarins reduce the risk of cardiovascular and brain diseases because of their antioxidant activities. This study has been designed, for the first time, to evaluate the effect of known furanocoumarins oxypeucedanin and isoimperatorin extracted from Prangos ferulacea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Previous studies suggested that OXY, OST, and ISO led to anticancer activities and induced apoptosis by activating caspase-3, -8, and -9 proteins in various types of human cancer cells, including DU145 [33], CD133 [34], PC-3, H1299 [35]. In contrast, one study revealed that OXY and ISO decrease caspase-3 activity, increase MMP, and demonstrate a protective effect against doxorubicin-induced apoptosis and neurotoxicity in PC-12 cells [36]. As seen in Fig.…”
Section: Caspase-3 Activitymentioning
confidence: 97%
“…Previous studies suggested that OXY, OST, and ISO led to anticancer activities and induced apoptosis by activating caspase-3, -8, and -9 proteins in various types of human cancer cells, including DU145 [33], CD133 [34], PC-3, H1299 [35]. In contrast, one study revealed that OXY and ISO decrease caspase-3 activity, increase MMP, and demonstrate a protective effect against doxorubicin-induced apoptosis and neurotoxicity in PC-12 cells [36]. As seen in Fig.…”
Section: Caspase-3 Activitymentioning
confidence: 97%
“…3,4 OXY was reported to have anti-mutagenic, cytotoxic, and antiproliferative activities against several cancer cells, including colon, breast, liver, and lung cancers. [5][6][7] Cancer cells need more significant biosynthetic components and building blocks, including amino acids and nucleotides, than normal cells due to their uncontrolled and highly proliferative cell division characteristics. Also, the expression of proapoptotic proteins is lower in cancer cells than in normal cells, which makes cancer cells more resistant to anti-cancer treatments and molecules.…”
mentioning
confidence: 99%